A Decade of Design: The Global Invention of the Kanga, 1876–1886. (2nd January 2017) - Ryan, MacKenzie Moon
Abstract : This article examines the early development of printed and manufactured cotton kanga textiles, worn popularly throughout East Africa by women as wrappers. Using archival, pictorial and object collections, I suggest that the decade from 1876 to 1886 was crucial for design. The bold colour and graphics of East African women's cloth printing, Indonesian batik motifs, European-printed handkerchief-style borders and the inclusion of text combined by 1886 to form the now standard composition of kanga cloth.